(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The intelligent organization is synonymous of a company that the mandate to develop the knowledge and the competitions of the people with loud value, that it is characterized for a net in continuous expansion of his human capital improving of continuous form the handling of abilities, has attitudes, knowledge and understanding of the surroundings; Through cultivation and expansion of the employers of thoughts where the collective aspiration is to learn how to work as a team to create the results that are desired in terms of quality, with the social linkage’s progressive identification, that is, reinforces the links that join them. You are for it, than the present essay XXI. attempts to examine the organizations based in intelligence, like an approximation to an entrepreneurial reality of the century the hermeneutics for the analysis of the theoretic contentses utilized a descriptive methodology and documentary, postulate itself For which. Stroke of ball mentioning than the study, it allowed coming to an end than the management of the century XXI, today more than ever she must pay attention to the role that you must perform in behalf of the company’s human factor, looking for the way to achieve a cohesion of group, knowledge to utilize all of the tools that the executive coaching provides him. Knowing how to utilize besides, of efficient form, all of the legacy of knowledge that must be put in the center in the man’s present-day behavior in the organizations manifesting his importance that way and implications in the organizational and space related to management, I eat also in the change processes planned within the companies with capability of learning.